1994
DOI: 10.1002/tea.3660311006
|View full text |Cite
|
Sign up to set email alerts
|

Learning science in a cooperative setting: Academic achievement and affective outcomes

Abstract: A learning unit in earth science was taught to high school students, using a jigsaw-group mastery learning approach. The sample consisted of 73 students in the experimental group and 47 students who learned the topic in an individualized mastery learning approach. The study lasted 5 weeks. Pretests and posttests on academic achievement and affective outcomes were administered. Data were treated with an analysis of covariance. The results show that students of the experimental group achieved significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 14 publications
(6 reference statements)
6
39
1
7
Order By: Relevance
“…Bu bulgular diğer araştırma sonuçları ile de desteklenmektedir (Okebukola, 1986;Baird, Lazarowitz & Lazarowitz, 1992;Heady, 1993;Lazarowitz, Lazarowitz & Baird, 1994;Posner & Markstein, 1994;Zales & Colosi, 1996;Trautwein, Racke & Hillman 1997;Colosi & Zales, 1998;Koprowski & Perigo, 2000).…”
Section: Results and Suggestionunclassified
“…Bu bulgular diğer araştırma sonuçları ile de desteklenmektedir (Okebukola, 1986;Baird, Lazarowitz & Lazarowitz, 1992;Heady, 1993;Lazarowitz, Lazarowitz & Baird, 1994;Posner & Markstein, 1994;Zales & Colosi, 1996;Trautwein, Racke & Hillman 1997;Colosi & Zales, 1998;Koprowski & Perigo, 2000).…”
Section: Results and Suggestionunclassified
“…In the process of experimenting, students are involved in observation, measurement, classification, recording data, forming hypotheses and data creation methods, changing and controlling variables. In addition, laboratory practice not only fosters academic achievement [8] but also contributes to meaningful learning by encouraging interpretation of knowledge [2][3][4][5][6][7][8][9]. It has also been found that the majority of students think that experiments are very helpful in their courses and learning by hands-on activities is the best and the most permanent way of learning for them [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Goodlad (1974), all learning is individual learning and there may be no other kind (Lazarowitz, Hertz-Lazarowitz & Baird, 1994).…”
Section: Discussionmentioning
confidence: 99%